(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the remineralization efficacy of 1450 ppm Sodium Fluoride (NaF) toothpaste on early caries lesion (ECL) of permanent teeth among students aged 6-15 on Ngoc Vung Island, Quang Ninh. Subjects and methods: A non-controlled clinical intervention study with a before-after design was conducted on ECLs from 70 students. Participants were instructed to brush twice daily with 1450 ppm NaF toothpaste using the modified Bass technique under supervision for 6 months. Efficacy was assessed based on the change in severity of 33 ECLs (D1, D2 levels) measured by the Diagnodent 2190 device at baseline (T0) and after 6 months (T1). Data were analyzed using SPSS 26.0. Results: After 6 months, the analysis of the 33 lesions showed that 12.5% of initial D1 lesions recovered completely (to D0) and 28.1% remained stable (D1). Among initial D2 lesions, 15.6% improved to D0 and 37.5% improved to D1. The remineralization effect was statistically significant and most pronounced in the molar region (p < 0.001). Conclusion: The usage of 1450 ppm Sodium Fluoride toothpaste is effective in promoting remineralization, improving, and stabilizing early caries lesions on the permanent teeth of children, especially in high-risk areas like molars. This is a feasible and effective intervention for school-based oral health programs in disadvantaged areas such as islands.